Feedforward Amplifiers for Wideband Communication Systems - Legarda, Jon. (Springer US : Imprint: Springer, 2006)
Feedforward Amplifiers for Wideband Communication Systems has been possible thanks to the research carried out throughout several years in the field of the linearization techniques applied to digital communication systems, particularly to those with high spectral efficient modulation techniques. The wireless telecommunications are more and more demanded for the Information Society. Such requirements are reflected as a great many of communication standards with specific coverage applications and, above all, with higher and higher data transmission rates. The electromagnetic spectrum, nevertheless, is a scarce asset that can not be spread and despite the increasingly tendency to transmit in higher frequencies, the bandwidths assigned to each application are always exploited to the limit. Feedforward Amplifiers for Wideband Communication Systems merges in the need of developing frequency efficient modulations with widespread codification techniques that result in wideband communication systems, with strict regulations in the usable frequency bandwidths and tight restrictions in the spurious emissions over the remaining spectrum. The radio frequency transmitters do not remain impassive to those changes, especially the power amplifiers, which efficiency and linearity directly determines the correct performance of the entire transmission system. The linearity specifications are commonly fixed by the telecommunication standards while the efficiency rates directly strikes the commercial viability of these transmitters. Feedforward Amplifiers for Wideband Communication Systems tries to put into practice the Feedforward linearization technique, aimed at improving either the linearity or efficiency parameters of power amplifiers, just intended for achieving a trade-off between the distortion specifications of the telecommunication standards and the efficiency enhancement of the transmission systems, which set, respectively, the linearity and the output level requirements of power amplifiers. This challenge is enshrined in one of the present wideband communication systems, but all the recommended design guidelines are perfectly reusable in the future wideband applications.